2016
DOI: 10.1371/journal.pone.0167554
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Gene Rpd3 Is Required for Starvation Stress Resistance

Abstract: Epigenetic regulation in starvation is important but not fully understood yet. Here we identified the Rpd3 gene, a Drosophila homolog of histone deacetylase 1, as a critical epigenetic regulator for acquiring starvation stress resistance. Immunostaining analyses of Drosophila fat body revealed that the subcellular localization and levels of Rpd3 dynamically changed responding to starvation stress. In response to starvation stress, the level of Rpd3 rapidly increased, and it accumulated in the nucleolus in what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…According to the KEGG analysis, the N. cucumeris genome harbours at least 108 genes associated with DNA damage-repair such as base/nucleotide excision repairand mismatch repair (Additional file 1: Table S32). In addition to these functional genes, some signal transduction pathways and epigenetic regulation could also play important roles in stress resistence, such as histone deacetylation [130132].…”
Section: Resultsmentioning
confidence: 99%
“…According to the KEGG analysis, the N. cucumeris genome harbours at least 108 genes associated with DNA damage-repair such as base/nucleotide excision repairand mismatch repair (Additional file 1: Table S32). In addition to these functional genes, some signal transduction pathways and epigenetic regulation could also play important roles in stress resistence, such as histone deacetylation [130132].…”
Section: Resultsmentioning
confidence: 99%
“…ChIP analysis has demonstrated that Rpd3 binds to the rDNA promoter. Rpd3 upregulates rRNA synthesis, whereas a Rpd3 knockdown reduces the number of polysomes during starvation (Nakajima et al, 2016). Also, knockdown flies die faster in response to starvation.…”
Section: Nucleolar Factors and Nucleolar Stress In The Regulation Of mentioning
confidence: 99%
“…Similarly, Esa1p, the yeast homolog of mammalian Tip60, catalyzes the hyperacetylation of Atg3, which enhances its interaction with Atg8 and facilitates Atg8 lipidation as well as autophagosome maturation under starvation conditions [ 41 ]. Protein acetylation and deacetylation are suggested in diapause [ 15 ], circadian rhythm [ 28 , 29 ], stress resistance and innate immunity in insects [ 14 , 15 ]. In Drosophila , the Tip60 protein complex promotes germline stem cell daughter differentiation in females [ 42 ], whereas, the regulatory mechanisms of Tip60 homologs in autophagy are not well documented in insects.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, sirtuin 1 (SIRT1), histone deacetylase 6 (HDAC6), and HDAC1 deacetylate ATG proteins such as ATG5, ATG7, LC3/Atg8 promote autophagy [ 11 , 12 , 13 ]. Mammalian HDAC homologies such as Rpd3, HDAC1, HDAC3, HDAC6, and SIRT2 are suggested to link with stress resistance in Drosophila melanogaster , development in Sarcophaga bullata , and phase polymorphism in locusts [ 14 , 15 , 16 ]. Moreover, parasitoids are more likely to suppress host immune systems and development by impeding histone acetylation and deacetylation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%